AN OBSERVATIONAL STUDY ON THE RELATIONSHIP BETWEEN NUTRITIONAL STATUS, SERUM IL-6, AND CRP LEVELS IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE AND DISEASE SEVERITY. - Suresh Sharma; Paresh Kumar Sarma; Gaurav Kumar Singh; Chayanika Rajbongshi; Sagnik Chakrabarty; Mogbul Hussain (Student's Journal of Health Research, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is an inflammatory disease that affects the entire body. We examined whether serum inflammatory markers, C-reactive protein (CRP), leptin, and nutritional status (as measured by serum levels of prealbumin and anthropometry) were associated with COPD severity. Methods: This hospital-based observational study was conducted on patients with chronic obstructive pulmonary disease (COPD) from Barpeta and the adjacent areas who were attending the Medicine Department of Fakhruddin Ali Ahmed Medical College and Hospital. From September 1, 2020, to August 31, 2021, a total of 60 cases were examined. Results: The majority of the cases were between the ages of 51 and 70. The preponderance of the 60 cases in the study, or 71.67 percent, were male. In the age range of 61 to 70, the prevalence of exertional dyspnea and the severity of COPD were the highest. Conclusion: As the severity of COPD increased, so did the concentration of inflammatory markers in the serum and the nutritional status of the patients.